2006
DOI: 10.1369/jhc.6a7087.2006
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin Upregulation and Polymerization by Transglutaminase 2 in Calcified Arteries of Matrix Gla Protein-deficient Mice

Abstract: S U M M A R Y Matrix Gla protein (MGP) is a potent inhibitor of soft tissue calcification, and Mgp gene deletion in mice results in arterial calcification. Our aim was to examine osteopontin (OPN) expression and localization, and posttranslational processing of OPN by the crosslinking enzyme transglutaminase 2 (TG2), in the calcified aorta of Mgp-deficient (Mgp 2/2 ) mice. Using immunohistochemistry and light and electron microscopy, we report that following mineralization occurring in the arterial media of Mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
61
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 61 publications
7
61
1
Order By: Relevance
“…In bone, tTG2 is expressed by osteoblasts (Al-Jallad et al, 2006;Nurminskaya and Kaartinen, 2006), and its crosslinking activity plays a role in the organisation of extracellular matrix. On the contrary, a combined increased expression of tTG2 and osteopontin has been detected in calcifi ed arteries of Gla-deficient mice, a model characterised by ectopic mineral deposition: this phenomenon has been interpreted as an inducible inhibitory mechanism of calcifi cation (Kaartinen et al, 2007). In the same model, osteopontin was expressed close to macrophages, prompting the authors to suggest that osteopontin oligomers created by tTG2 may constitute a scaffold for macrophage adhesion and calcifi cation resorption (Kaartinen et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In bone, tTG2 is expressed by osteoblasts (Al-Jallad et al, 2006;Nurminskaya and Kaartinen, 2006), and its crosslinking activity plays a role in the organisation of extracellular matrix. On the contrary, a combined increased expression of tTG2 and osteopontin has been detected in calcifi ed arteries of Gla-deficient mice, a model characterised by ectopic mineral deposition: this phenomenon has been interpreted as an inducible inhibitory mechanism of calcifi cation (Kaartinen et al, 2007). In the same model, osteopontin was expressed close to macrophages, prompting the authors to suggest that osteopontin oligomers created by tTG2 may constitute a scaffold for macrophage adhesion and calcifi cation resorption (Kaartinen et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, a combined increased expression of tTG2 and osteopontin has been detected in calcifi ed arteries of Gla-deficient mice, a model characterised by ectopic mineral deposition: this phenomenon has been interpreted as an inducible inhibitory mechanism of calcifi cation (Kaartinen et al, 2007). In the same model, osteopontin was expressed close to macrophages, prompting the authors to suggest that osteopontin oligomers created by tTG2 may constitute a scaffold for macrophage adhesion and calcifi cation resorption (Kaartinen et al, 2007). The effect of osteopontin on resorption is further supported by the observation that, in osteopontin KO mice, administration of recombinant osteopontin induced resorption of ectopic calcifi cations (Steitz et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Kaartinen and colleagues (38) reported that MGP-deficient mice demonstrated arterial calcification, OPN upregulation, and macrophage migration and concluded that macrophages adhere to calcified elastic lamellae to promote the clearance of ectopic mineral deposits. However, there are few reports about the involvement of MGP in kidney stones.…”
Section: Discussionmentioning
confidence: 99%
“…3 In MgpÀ/À mice, OPN initiates removal of the mineral by macrophages. 37 Of note, macrophages have also been found to be abundant near calcified areas in PXE dermis. 38 MGP has been shown to negatively regulate BMP2, a known osteoinductive protein.…”
Section: Vk-dependent Proteins In Pxe Patientsmentioning
confidence: 98%